Child Maltreatment and Psychiatric Disorders Increase Risk for Stalking Victimization - Bonagura, Alexandra Grace (Journal of interpersonal violence, 2023)
Stalking is a serious public health problem, estimated to affect about 15% of women and 6% of men. Victims of stalking have been reported to be at increased risk for psychological distress, depression, lowered social and daily functioning, and other forms of victimization. The present study sought to determine whether individuals with documented histories of childhood maltreatment and those with psychiatric disorders are at increased risk for stalking victimization. Participants included maltreated children and matched controls (N = 892) from a Midwestern, metropolitan area who were followed up into adulthood. Psychiatric disorders (major depressive disorder, post-traumatic stress disorder, antisocial personality disorder, and substance use disorders) were assessed at mean age 29 and borderline personality disorder at age 39. Participants reported lifetime stalking using the Lifetime Trauma and Victimization History instrument and based on a separate measure, past year intimate partner stalking victimization. Analyses controlled for sex, race, and age. Depression, PTSD, antisocial, and borderline personality disorders were associated with increased lifetime risk for stalking victimization. Childhood maltreatment, neglect, and psychiatric disorders (substance use, PTSD, antisocial personality, and borderline personality) predicted increased risk for past year stalking victimization. Findings indicated sex differences in lifetime risk of stalking victimization and race differences in past-year stalking victimization. Although the results reveal relationships among child maltreatment, psychiatric disorders, and stalking victimization, the impact of childhood maltreatment is most salient in terms of past year intimate partner stalking victimization, and particularly for individuals with histories of neglect. Future research is needed to better understand these race and sex differences in stalking victimization.